Electrolyte additive, electrolyte and lithium battery
Patent Information
- Application Number
- CN202610839118.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-10-16
AI Technical Summary
电解质在高压下更容易氧化分解,这将加剧锂离子电池电化学性能的不断恶化和寿命衰减
[0021] As a further improvement to the above-described scheme of the present invention, the active material of the positive electrode is LiNi. x Co y Mn z O2, where x, y, and z represent the mole fractions of nickel, cobalt, and manganese, respectively, and x + y + z = 1. The active material of the negative electrode is graphite. The lithium battery has a charging cut-off voltage ≥ 4.3V and exhibits good cycle stability and capacity retention.
Smart Images

Figure SMS_1 
Figure SMS_11 
Figure SMS_12
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to an electrolyte additive, an electrolyte, and a battery. Background Technology
[0002] With the rapid development of new energy electric vehicles, the low-altitude economy, and portable consumer electronics, higher demands are being placed on the performance of lithium-ion batteries. In particular, to address the range anxiety of electric vehicles and the challenges of emerging applications such as lightweight low-altitude aircraft, there is an urgent need to improve the energy density of lithium-ion batteries, a key performance indicator.
[0003] To further improve battery energy density, increasing the operating cutoff voltage of existing cathode materials or developing new cathode materials with higher voltage and capacity would be more effective methods. However, the narrow electrochemical window of the current LiPF6-carbonate electrolyte system has become a key factor limiting the further development of next-generation high-energy-density lithium-ion batteries. Specifically, increasing the battery operating voltage presents challenges for lithium-ion batteries, including material instability and severe interface problems between traditional electrolytes and electrode materials. Electrolytes are more prone to oxidative decomposition under high voltage, which will exacerbate the continuous deterioration of the electrochemical performance and lifespan degradation of lithium-ion batteries.
[0004] Therefore, in order to improve the electrochemical stability of high-nickel ternary lithium-ion batteries at high cutoff voltages, constructing a stable and robust positive and negative electrode electrolyte interface is an urgent problem to be solved in the development of high-energy-density lithium-ion batteries. Summary of the Invention
[0005] Based on this, the purpose of the present invention is to provide an electrolyte additive, an electrolyte, and a battery, which can effectively improve the stability of the electrode-electrolyte interface and the cycle performance of the battery under high cutoff voltage.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides an electrolyte additive, comprising a first additive and a second additive, wherein the first additive is a sulfur-containing additive, and the second additive has the structure shown in the following formula:
[0007] R1, R2, R3, R4 and R5 are each independently selected from any one of hydrogen atom, halogen, substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C2-C5 alkenyl, substituted or unsubstituted C2-C5 alkynyl, substituted or unsubstituted C1-C5 alkoxy, aryl, nitro, sulfonyl, sulfonate and cyano.
[0008] This invention significantly improves the oxidation resistance of the electrolyte, expands the electrochemical window of the electrolyte, and enhances the electrode-electrolyte interface stability and long-cycle performance of lithium-ion batteries under high voltage through the synergistic effect of the first and second additives.
[0009] As a further improvement of the above-mentioned solution of the present invention, the first additive is selected from at least one of vinyl sulfate, vinyl sulfite, 1,3-propanesulfonate lactone, 1,3-propenesulfonate lactone, methylene disulfonate, vinyl disulfate, 4-propyl vinyl sulfate, and lithium fluorosulfonate; preferably lithium fluorosulfonate.
[0010] As a further improvement to the above-described scheme of the present invention, the second additive is at least one of the compounds shown in Formula I to Formula IX: Formula I Formula II Formula III Formula IV Formula V Formula VI Formula VII Formula VIII Formula IX The CAS numbers for the compounds represented by Formula I, II, and IX are as follows: Formula I: 40465-45-0; Formula II: 16413-26-6; Formula III: 342617-80-5; Formula IV: 1261862-00-3; Formula V: 1261582-05-1; Formula VI: 1261438-96-3; Formula VII: 2369052-28-6; Formula VIII: 1261674-83-2; and Formula IX: 1261439-24-0.
[0011] The first additive of this invention is a sulfur-containing lithium salt or organic compound with a low LUMO energy level and a high HOMO energy level. It can be simultaneously oxidized / reduced on both the positive and negative electrode surfaces to form a solid electrolyte interphase (SEI) film containing Li2S / Li2SO4 / Li2SO3 / LiF and organic sulfides, thereby improving interfacial lithium-ion transport and suppressing negative electrode interface side reactions. The second additive contains functional groups such as isocyanate (O=C=N-) and cyano (N≡C-). The strong electron-withdrawing groups such as cyano can be effectively adsorbed on the surface of highly active cathode materials and repel solvent molecules, reducing the oxidative decomposition of solvent molecules on the cathode side. Furthermore, the isocyanate (O=C=N-) has high reactivity with trace amounts of H2O and HF in the electrolyte, which can reduce the corrosion of the electrode interface and cathode materials by harmful substances such as HF, thereby suppressing the undesirable structural evolution of the positive electrode material and significantly improving the cycle life and capacity decay of lithium-ion batteries under high voltage conditions.
[0012] As a further improvement to the above-described scheme of the present invention, the mass ratio of the first additive to the second additive is 0.2 to 5:1.
[0013] The present invention also provides an electrolyte comprising the electrolyte additives as described above. The electrolyte provided by the present invention can significantly improve the cycle performance of lithium-ion batteries at high voltages >4.3 V, achieving high voltage resistance while extending battery life.
[0014] As a further improvement to the above-described solution of the present invention, the content of the first additive in the electrolyte is 0.01wt% to 5wt%, and / or the content of the second additive is 0.01wt% to 5wt%.
[0015] As a further improvement to the above-described solution of the present invention, the content of the first additive in the electrolyte is 0.5wt%~2wt%, and / or the content of the second additive is 0.5wt%~2wt%.
[0016] As a further improvement to the above-described solution of the present invention, it further includes lithium salt and organic solvent; the content of lithium salt in the electrolyte is 10wt%~15wt%.
[0017] As a further improvement to the above-described scheme of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorobis(oxalate) phosphate, lithium oxalate phosphate, lithium di(oxalate) borate, lithium difluoro(oxalate) borate, lithium bis(trifluorosulfonyl)imide, and lithium difluorosulfonylimide.
[0018] As a further improvement of the above-described solution of the present invention, the organic solvent is selected from at least one of cyclic carbonate solvents, chain carbonate solvents and ether solvents, and the cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate and difluoroethylene carbonate. The organic solvent also includes at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, isopropyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, ethyl butyrate, ethyl fluoroacetate, methyl difluoroacetate, ethyl difluoroacetate, ethyl trifluoroacetate, ethyl 2,2-difluoroacetate, ethyl 2,2,2-trifluoroacetate, and methyltrifluoroethyl carbonate. By optimizing the ratio of lithium salt and organic solvent, and using oxidation-resistant carbonates, carboxylic esters, or fluorinated solvents, the oxidation resistance of the electrolyte itself is improved, and the conductivity of the electrolyte is increased to promote lithium-ion transport and reduce interfacial side reactions.
[0019] The present invention also provides a lithium battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte is the electrolyte as described above.
[0020] As a further improvement of the above-mentioned solution of the present invention, the positive electrode sheet includes a positive electrode active material, which is selected from at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese oxide, and the negative electrode active material is selected from at least one of natural graphite, artificial graphite, silicon, and lithium titanate.
[0021] As a further improvement to the above-described scheme of the present invention, the active material of the positive electrode is LiNi. x Co y Mn z O2, where x, y, and z represent the mole fractions of nickel, cobalt, and manganese, respectively, and x + y + z = 1. The active material of the negative electrode is graphite. The lithium battery has a charging cut-off voltage ≥ 4.3V and exhibits good cycle stability and capacity retention.
[0022] The electrolyte provided by this invention can significantly improve the cycle performance of lithium-ion batteries at high voltages >4.3 V, achieving high voltage resistance while extending battery life. The first and second additives are preferentially oxidized to form components containing Li2S, Li2SO3, and organic sulfides, enhancing the oxidation stability of the electrode-electrolyte interface and suppressing undesirable side reactions at the cathode material interface. The high reactivity of the functional groups in the second additive allows it to react with trace amounts of water and free acid in the electrolyte, removing harmful impurities and effectively protecting the electrode interface and active materials, thus improving the battery's long-cycle stability. Detailed Implementation
[0023] To facilitate understanding of the present invention, a more comprehensive description will be provided below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to limit the invention.
[0025] Example 1 This embodiment proposes a lithium-ion battery, the preparation method of which includes: (1) Preparation of electrolyte The electrolyte in this embodiment includes a first additive, a second additive, a lithium salt, and a solvent. The first additive is lithium fluorosulfonate, and the second additive has the structure shown in Formula I:
[0026] Formula I The lithium salts are lithium hexafluorophosphate (LiPF6) and lithium bisfluorosulfonyl imide (LiFSI). The solvent is a homogeneous mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and methyl trifluoroethyl carbonate (FEMC) in a mass ratio of 2:5:3. In the electrolyte of this embodiment, lithium hexafluorophosphate (LiPF6) accounts for 12.5% of the total mass of the electrolyte, lithium bisfluorosulfonyl imide (LiFSI) accounts for 0.5% of the total mass of the electrolyte, the first additive accounts for 1% of the total mass of the electrolyte, and the second additive accounts for 0.5% of the total mass of the electrolyte.
[0027] The electrolyte preparation method in this embodiment is as follows: In an argon-filled glove box (with water and oxygen levels both <0.1ppm), ethylene carbonate (EC), methyl ethyl carbonate (EMC), and methyl trifluoroethyl carbonate (FEMC) are uniformly mixed at a mass ratio of 2:5:3 to obtain a solvent; then, fully dried lithium hexafluorophosphate (LiPF6) and lithium difluorosulfonyl imide (LiFSI) are added; after the lithium salt is completely dissolved, the first additive and the second additive are added to obtain the electrolyte.
[0028] (2) Preparation of the positive electrode sheet: LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1O2 (NCM811), polyvinylidene fluoride (PVDF), and conductive carbon black Super-p are mixed in a weight ratio of 98:1:1. N-methylpyrrolidone (NMP) is added, and the mixture is stirred under vacuum to obtain a positive electrode slurry. The positive electrode slurry is uniformly coated onto an aluminum foil with a thickness of 13 μm. After the aluminum foil is dried at room temperature, it is transferred to a forced-air oven at 120°C and dried for 12 hours. Then, it is rolled and slit to obtain a positive electrode sheet.
[0029] (3) Preparation of negative electrode sheet: The negative electrode active material artificial graphite, conductive carbon black, thickener carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) emulsion were mixed in a weight ratio of 96.5:1:1.5:1. Deionized water was added, and the mixture was stirred under vacuum to obtain a negative electrode slurry. The negative electrode slurry was uniformly coated onto a copper foil with a thickness of 8 μm. After the copper foil was dried at room temperature, it was transferred to a 100°C forced-air oven to dry for 12 hours. Then, it was rolled and slit to obtain a negative electrode sheet.
[0030] (4) Preparation of lithium-ion batteries: The separator is moved back and forth between the stacking platforms by a movable stacking stage, and the cut positive and negative electrode sheets are placed on them. The positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, with the separator positioned between the positive and negative electrode sheets to provide isolation. Then, it is placed in an aluminum-plastic film outer packaging foil, baked, and stored in a vacuum oven to complete the cell preparation. When in use, the electrolyte provided in this embodiment is injected, and after vacuum sealing, settling, formation, and capacity testing, lithium-ion battery testing can be performed.
[0031] Example 2-12 The difference between Examples 2-12 and Example 1 lies in the different types and amounts of additives in the electrolyte, as shown in Table 1.
[0032] Comparative Examples 1-15 The difference between Comparative Examples 1-15 and Example 1 lies in the different types and amounts of additives in the electrolyte, as shown in Table 1.
[0033] Test case The lithium-ion batteries of Examples 1-12 and Comparative Examples 1-15 were subjected to the following tests: 1C / 1C 25℃ 4.6V Cycling Performance Test: The lithium-ion batteries obtained in Examples 1-12 and Comparative Examples 1-15 were first placed in a 25℃ constant temperature chamber for 30 minutes, then charged at 1C constant current and constant voltage to 4.6V, with the constant voltage current ≤0.05C cutoff, and then placed for 30 minutes; then discharged at 1C times the constant current to 2.8V. This constitutes one charge-discharge cycle. The average discharge capacity of the first 5 cycles was taken as the initial discharge capacity. When the cycle reached 500 cycles, the cycle capacity retention rate was calculated as follows: Cycle capacity retention rate at 500 cycles = (Cycle discharge capacity at 500 cycles / Initial discharge capacity) × 100%. The test results are shown in Table 1.
[0034] Table 1 Electrolyte Additives and Battery Performance
[0035] The results in Table 1 show that: Cycling data at 25℃ and 4.6V show that, compared to high-voltage electrolytes using only the first additive or only the second additive, the high-voltage electrolytes provided in Examples 1-12 of this invention, which simultaneously contain both the first and second additives, significantly improve the cycle performance of ternary lithium-ion batteries at a high cutoff voltage of 4.6V when applied to ternary lithium-ion batteries. The capacity retention rate of Examples 1-12 after 500 cycles is significantly better than that of Comparative Examples 1-15 using a single additive or without additives. This is due to the optimized combination of organic solvents, which regulates the ionic conductivity of the electrolyte and improves the thermal stability of the solvent, as well as the excellent interface improvement capabilities of the first and second additives. On the one hand, by combining high-voltage resistant solvents and high dielectric constant solvents, the conductivity of the electrolyte is improved and the oxidation stability of the high-voltage electrolyte is enhanced, thereby reducing the oxidation reaction of the electrolyte. The first additive is a sulfur-containing lithium salt or organic compound with a low LUMO energy level and a high HOMO energy level. It can be simultaneously oxidized / reduced on both the positive and negative electrode surfaces to form a solid electrolyte interphase (SEI) film containing Li₂S / Li₂SO₄ / Li₂SO₃ / LiF and organic sulfides. This forms a dense and stable passivation layer, improving interfacial lithium-ion transport and suppressing side reactions at the negative electrode interface. This reduces side reactions between the electrode and the electrolyte, as well as the consumption of active lithium. Similarly, its high HOMO energy level preferentially oxidizes and forms a film at the high potential of the positive electrode, inhibiting the oxidative decomposition of the electrolyte on the surface of the highly active cathode material, thereby improving the stability of the positive electrode. Furthermore, the second additive contains functional groups such as isocyanate (O=C=N-) and cyano (N≡C-). The strong electron-withdrawing groups, such as the cyano group, can effectively adsorb onto the surface of the highly active cathode material and repel solvent molecules, reducing the oxidative decomposition of solvent molecules on the cathode side. Moreover, the isocyanate (O=C=N-) group has high reactivity with trace amounts of H2O and HF in the electrolyte, which can reduce the corrosion of the electrode interface and cathode material by harmful substances such as HF. Therefore, the technical solution provided by this invention significantly improves the capacity decay of lithium-ion batteries at high cutoff voltages and enhances battery cycle life.
[0036] The test results of Examples 1-7 show that in the high-voltage electrolyte provided by the present invention, when the amount of the first additive lithium fluorosulfonate is fixed and the content of Compound I additive is gradually increased, the high-voltage cycle capacity of the corresponding battery maintains a trend of first increasing and then decreasing. The test results of Examples 2 and 5-7 show that when the content of the second additive is fixed and the content of the first additive is gradually increased, the high-temperature cycle performance of the corresponding battery also shows a trend of first increasing and then decreasing. This indicates that excessive amounts of the first and second additives are not conducive to the improvement of electrode interface and battery performance. When the first and second additives are in a suitable addition ratio, the battery can be guaranteed to have excellent cycle performance at high voltage.
[0037] The test results of Examples 8-12 and Comparative Examples 12-15 show that the lithium-ion batteries obtained by combining different types of first additives and different types of second additives in the high-voltage electrolyte system provided by the present invention all have good cycle performance, indicating that the different first additives and second additives contained in the high-voltage electrolyte system provided by the present invention have universality.
[0038] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0039] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. An electrolyte additive, characterized in that, The electrolyte additive includes a first additive and a second additive, wherein the first additive is a sulfur-containing additive; and the second additive has the structure shown in the following formula: R1, R2, R3, R4 and R5 are each independently selected from any one of hydrogen atom, halogen, substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C2-C5 alkenyl, substituted or unsubstituted C2-C5 alkynyl, substituted or unsubstituted C1-C5 alkoxy, aryl, nitro, sulfonyl, sulfonate and cyano.
2. The electrolyte additive according to claim 1, characterized in that, The first additive is selected from at least one of vinyl sulfate, vinyl sulfite, 1,3-propanesulfonate lactone, 1,3-propenesulfonate lactone, methylene disulfonate, vinyl disulfate, 4-propyl vinyl sulfate, and lithium fluorosulfonate.
3. The electrolyte additive according to claim 1, characterized in that, The second additive is at least one of the compounds shown in Formula I to Formula IX: Formula I Formula II Formula III Formula IV Formula V Formula VI Formula VII Formula VIII Formula IX .
4. The electrolyte additive according to claim 1, characterized in that, The mass ratio of the first additive to the second additive is 0.2 to 5:
1.
5. An electrolyte, characterized in that, The electrolyte includes the electrolyte additive as described in any one of claims 1-4.
6. The electrolyte according to claim 5, characterized in that, In the electrolyte, the content of the first additive is 0.01wt% to 5wt%, and / or the content of the second additive is 0.01wt% to 5wt%.
7. The electrolyte according to claim 6, characterized in that, In the electrolyte, the content of the first additive is 0.5wt% to 2wt%, and / or the content of the second additive is 0.5wt% to 2wt%.
8. The electrolyte according to claim 5, characterized in that, The electrolyte also includes lithium salt and organic solvent; the content of lithium salt in the electrolyte is 10wt%~15wt%.
9. The electrolyte according to claim 8, characterized in that, The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorobis(oxalate) phosphate, lithium oxalate phosphate, lithium di(oxalate) borate, lithium difluorobis(oxalate) borate, lithium bis(trifluorosulfonyl)imide, and lithium difluorosulfonylimide. The organic solvent is selected from at least one of cyclic carbonate solvents, chain carbonate solvents, and ether solvents, and the cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate, and difluoroethylene carbonate. The organic solvent further includes at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, isopropyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, ethyl butyrate, ethyl fluoroacetate, methyl difluoroacetate, ethyl difluoroacetate, ethyl trifluoroacetate, ethyl 2,2-difluoroacetate, ethyl 2,2,2-trifluoroacetate, and methyl trifluoroethyl carbonate.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte as described in any one of claims 1-9.
11. The lithium-ion battery according to claim 10, characterized in that, The positive electrode includes a positive electrode active material, which is selected from at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium-rich manganese oxide; the negative electrode active material is selected from at least one of natural graphite, artificial graphite, silicon, and lithium titanate.